2004
DOI: 10.1196/annals.1297.017
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Transcriptional Responses to Oxidative Stress in the Heart of Aged C57BL/6 Mice

Abstract: To investigate the transcriptional response to oxidative stress in the heart and how it changes with age, we examined the cardiac gene expression profiles of young (5 months old), middle-aged (15 months old), and old (25 months old) C57BL/6 mice treated with a single intraperitoneal injection of paraquat (50 mg/kg). Mice were killed at 0, 1, 3, 5, and 7 hours after paraquat treatment, and the gene expression profile was obtained with high-density oligonucleotide microarrays. Of 9,977 genes represented on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The increased levels of ROS produced by oxidative stress are known to induce expression of multiple genes, including PGC-1α and GADD45 (26,27). In parallel with the increased level of ROS in Sirt3 KD cells, there were significant increases in expression of these genes in the basal state, and these were further enhanced after H 2 O 2 treatment with no change in Sirt3 mRNA expression (Fig.…”
Section: Sirt3 Knockout Mice Exhibit Impaired Insulin Signaling and Imentioning
confidence: 84%
“…The increased levels of ROS produced by oxidative stress are known to induce expression of multiple genes, including PGC-1α and GADD45 (26,27). In parallel with the increased level of ROS in Sirt3 KD cells, there were significant increases in expression of these genes in the basal state, and these were further enhanced after H 2 O 2 treatment with no change in Sirt3 mRNA expression (Fig.…”
Section: Sirt3 Knockout Mice Exhibit Impaired Insulin Signaling and Imentioning
confidence: 84%
“…Several studies have identified age-associated downregulation of genes involved in metabolism, mitochondrial function, protein synthesis, processing, transport and turnover [8, 27, 30, 34, 38, 65, 66], consistent with the loss of proteostasis and mitochondrial dysfunction identified as hallmarks of aging [1]. Intriquingly, genes associated with mitochondrial function are also implicated in longevity [55, 67, 68].…”
Section: What Types Of Genes Show Age-associated Changes In Expression?mentioning
confidence: 99%
“…As a result, aging increases wall stress that is not normalized by ventricular remodeling 36 . Furthermore, induction of cell protective mechanisms, such as expression of anti-oxidant and heat shock proteins, in response to pathologic insults is attenuated in aging hearts 33, 37, 38 . Optimal therapeutic interventions to alleviate the adverse effects of aging should prevent cell death and accumulation of senescent myocytes 22 .…”
Section: Manifestation Of Aging In the Heartmentioning
confidence: 99%